PERTANGGUNGJAWABAN PIDANA TERHADAP PERS YANG MELAKUKAN TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI KORAN - Wulan Ratna Sari; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The enactment of the Criminal Code in the case of the press, then the criminal liability also applies. Responsible parties must also be determined on the basis of a criminal responsibility system under the Penal Code. In this case relates to criminal liability for criminal defamation through Koran. The purpose of writing this thesis, namely: first, criminal liability to the press who committed criminal defamation through the newspaper, Second, who is responsible related to criminal liability to the press who committed criminal defamation through the newspaper.The type of research used in this study is a normative legal research. Normative legal research is a literary legal research. In this study, data sources used, primary data, secondary data and tertiary data, data collection techniques in this study with literature study.From the results of this study indicates that the concept of Defamation in news in the newspaper occurred after the cooperation of parties who served in news mempubikasikan. The legal subject who can be held criminally liable for defamation in the news in newspapers are journalists, editors, chief editors and printers. Suggestion of the author, Firstly, the Press Law needs to be revised in order to contain the explicitly defamation of defamation so as not to be multiple interpretation; Secondly, in determining the subject of criminal responsibility law should be applied the principle of mistake and the principle of participation so that the offender of defamation can be given sanction in accordance with applicable laws and regulations, Third, the press company must have standard procedures related to the technical publication of the news so that the mechanism of accountability can be clearly identified.Keywords: Accountability-Crime-Press-Crime-Pollution-Name-Good